Larval susceptibility of Aedes (Stegomyia) albopictus (Diptera: Culicidae) from São Paulo, Brazil to Bacillus thuringiensis var israelensis H-141 - DUQUE-L., JONNY E.; NAVARRO-SILVA, MARIO ANTÔNIO (Revista Colombiana de Entomología, 2005)
The susceptibility of Aedes albopictus larvae, originating from “Vale do Ribeira Ilha Cumprida” São Paulo, Brasil, was determined under laboratory conditions. The product used was Bacillus thuringiensis var israelensis H-14 Vectobac–AS with 1,200 international toxic units (TU) per milligram. An Aedes aegypti Rockefeller colony from CDC (Center for Disease Control) of Puerto Rico was used as a reference. Lethal concentrations determined for Ae. albopictus were LC50= 0.12 ppm and LC90= 0.28 ppm and for the reference species Ae. aegypti they were LC50 0.07 ppm and LC95 0.17 ppm. It is concluded that Ae. albopictus presented a different response to the bioinsecticide than Ae. aegypti.